1992
DOI: 10.1038/bjc.1992.430
|View full text |Cite
|
Sign up to set email alerts
|

The combination of radiotherapy, adjuvant chemotherapy (cyclophosphamide-doxorubicin-ftorafur) and tamoxifen in stage II breast cancer. Long-term follow-up results of a randomised trial

Abstract: Summary Two hundred patients with node positive stage II breast cancer were randomised to four groups after radical mastectomy and axillary evacuation: (1) Postoperative radiotherapy, (2) Adjuvant chemotherapy with eight courses of CAFt (cyclophosphamide 500 mg m-2 + doxorubicin 40 mg/m-2 + ftorafur 20 mg kg-' orally day 1-14) every fourth week, (3) Postoperative radiotherapy and adjuvant chemotherapy and (4) postoperative radiation, adjuvant chemotherapy and tamoxifen 40 mg daily for 2 years.Thirty-two per ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(7 citation statements)
references
References 32 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…Ahmann et al, reported that combined chemohormonal therapy with Tam, Dox and cyclophosphamide resulted in a higher objective response rate and a long median survival in patients with ER-positive tumors [24]. Similarly, another study found that the combination of radiotherapy, Dox and Tam seemed to improve both relapse-free and overall survival in ER-positive tumors [5]. The results of this study tend to support the findings of the two earlier with respect to the synergistic effect on cell survival in ER-positive breast cancers, but not in ER-negative breast cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ahmann et al, reported that combined chemohormonal therapy with Tam, Dox and cyclophosphamide resulted in a higher objective response rate and a long median survival in patients with ER-positive tumors [24]. Similarly, another study found that the combination of radiotherapy, Dox and Tam seemed to improve both relapse-free and overall survival in ER-positive tumors [5]. The results of this study tend to support the findings of the two earlier with respect to the synergistic effect on cell survival in ER-positive breast cancers, but not in ER-negative breast cancers.…”
Section: Discussionmentioning
confidence: 99%
“…It is classified as an anticancer anthracycline antibiotic and is commonly used in the treatment of multiple cancers, including bladder cancer, breast cancer, ovarian cancer, lung cancer and gastric cancer [1][2][3][4]. However, several randomized clinical studies have included this drug in adjuvant regimens, possibly because of a fear of long-term cardiotoxicity [5]. Tam is a nonsteroidal selective estrogen receptor modulator that is widely used in the treatment of hormone-dependent breast cancers.…”
Section: Introductionmentioning
confidence: 99%
“…This irradiation technique was designed for treating the whole chest wall and electron energies between 4 and 15 MeV were used, according to the minimal thickness of the chest wall (skin-surface to lung). Higher incidences of symptomatic radiation pneumonitis have also been reported in series in which a photon "hockey-stick" field was used to treat the internal mammary lymph nodes concurrently with chemotherapy [2]. Symptomatic pneumonitis occurred in only one of 164 irradiated patients in the British Columbia trial, in which chemotherapy and postmastectomy radiotherapy were given sequentially [30].…”
Section: Discussionmentioning
confidence: 98%
“…Finally, there appears to be individual variability in susceptibility to radiation injury, as there are several reports of severe pneumonitis developing after relatively small doses of radiation. 109,110,[118][119][120][121][122][123] One might question whether such increased susceptibility is related pathogenetically to the uncommon occurrence of extensive radiation pneumonitis beyond the radiation field. A trivial explanation for these events is that they result from technical errors involving radiation port placement.…”
Section: Overview Of Noninfectious Causes Of the Febrile Pneumonitis ...mentioning
confidence: 99%